Studi Deskriptif Peranan Orang Tua Dan Sekolah Dalam Ekstrakurikuler Seni Tari Di Sekolah Dasar - Ekzu Semesti Seta; Bambang Parmadi; Dwi Anggraini (Universitas Bengkulu, 2020)
The purpose of this study is to describe the role of parents and schools in extracurricular dance activities in public elementary schools 08 Bengkulu city. This type of research is descriptive qualitative. The subjects of this study were the parents of students who took extracurricular dance and dance teachers in public elementary schools 08 Bengkulu city. The instruments used are the observation sheet and interview sheet. Data collection techniques using observation, interviews and documentation. The data obtained were analyzed by means of Miles, Huberman, and Saldana models, namely data collection, data condensation, data display and data verification. The results of this study are the role of parents 1. Parents as guides. The results obtained are parents guiding children by training children in dance movements directly during dance practice and mutual respect and respect, 2. Parents as motivators, parents motivate by advising children so that they are more serious when practicing dance, appreciating children with prizes, parents motivate children by seeing children practice dance directly and parents motivate children by paying for the attributes of competitions and performances. 3. Parents as givers of attention, from the results obtained that parents provide motivation by escorting children during training, parents, accompanying children during training and competitions and parents giving attention to children in the form of praise or encouragement. While the role of the school, namely 1. The teacher as a guide includes educating, training and evaluating students' extracurricular training activities 2. The teacher as a motivator 3. The teacher as an evaluator 4. The teacher as an administrative service. The teacher educates students to be responsible, fosters self-confidence, the teacher trains floor movements and patterns directly, the teacher also gives confidence to students for peer tutors and provides criticism and suggestions when students are less focused on dance practice.Keywords: ance extracurricular activities, the role of parents and schools